2018
DOI: 10.1097/pcc.0000000000001532
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Simulation Boot Camp for Pediatric Cardiac Critical Care Nurse Practitioners*

Abstract: Although simulation boot camps have been used effectively for training physicians and educating critical care providers, this was a novel approach to educating pediatric nurse practitioners from multiple academic centers. The course improved overall knowledge, and the pediatric nurse practitioners reported satisfaction and confidence in the simulation experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
1
30
0
3
Order By: Relevance
“…In prehealth education, effective apprenticeship is an important step to integrate theory into practice. Recently, schools have started to use augmented/virtual reality, robot technology and computerized simulation, such as Shadow Health, for distance online simulation (de Oliveria, do Prado, & Kempfer, 2014;Aebersold, 2018;Brown et al, 2018). As technology advances in this area, we have to be prepared to incorporate innovations, but also do the research needed to determine how clinical competency is measured, what means should be used, and how often students need these experiences (Sittner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prehealth education, effective apprenticeship is an important step to integrate theory into practice. Recently, schools have started to use augmented/virtual reality, robot technology and computerized simulation, such as Shadow Health, for distance online simulation (de Oliveria, do Prado, & Kempfer, 2014;Aebersold, 2018;Brown et al, 2018). As technology advances in this area, we have to be prepared to incorporate innovations, but also do the research needed to determine how clinical competency is measured, what means should be used, and how often students need these experiences (Sittner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial comparing blended vs. online clinical supervision for undergraduate nursing students found that students in blended courses were more satisfied with their learning experience compared to those in the online courses (McCutcheon, O'Halloran, & Lohan, 2018). Evidence shows that there is a need for high fidelity clinical simulations in nursing education (Hayden, Smiley, Alexander, Kardong-Edgren, & Jeffries, 2014;La Cerra et al, 2019;Brown et al, 2018) and the International Nursing Association for Clinical Simulation and Learning recommends setting standards for best practice for simulation in online nursing programs to ensure clinical competency (Sittner et al, 2015). In the meantime, simple strategies such as having online students come for onsite immersions where faculty can assess, teach, and evaluate clinical competency through simulation with mannequins can validate effectiveness of delivery methods.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation scenario was designed, implemented, and piloted at a large-scale simulationbased boot camp for advanced practice nurses. 11 An expert opinion survey was used to develop a checklist to establish priorities for scenario tasks (see Table ). This process involved content experts from the PCICU and the cardiac surgery department (physicians, nurses, and PNPs) who systematically evaluated the simulations before implementation to achieve consensus on the most critical Figure 1 In situ simulation room setup.…”
Section: Simulation Scenariomentioning
confidence: 99%
“…12,16,19 Abbreviations 22 With RCDP, both concepts are refined to augment the impact of the simulation experience in the allotted time frame. 8,11 In each ISS in this project, the facilitator had 30 minutes to teach the scenario checklist and convey the RCDP teaching method. Each 30-minute session involved cycling between simulation and deliberate practice and debriefing time.…”
Section: Rapid Cycle Deliberate Practicementioning
confidence: 99%
“…[4][5][6][7][8] Simulation boot camps for critical care and cardiology fellows and APPs have been reported. 5,[9][10][11] These courses lead to improvement in overall CICU knowledge and confidence when managing these complex patients. Simulation can also be used for skills training for CICU staff including procedural training, initiation of extracorporeal membrane oxygenation (ECMO), and management of ventricular assist devices.…”
Section: The Role Of Simulation In Cardiac Intensive Care Educationmentioning
confidence: 99%